204k views
1 vote
Please correct my work and show your work if I MESSED up

Please correct my work and show your work if I MESSED up-example-1
User Roozbubu
by
5.7k points

1 Answer

3 votes

If the first line says


\sqrt[3]{4x^3}\cdot\sqrt[3]{2x^4}

we should first write this as one cube root:


\sqrt[3]{4x^3\cdot2x^4}=\sqrt[3]{8x^7}

Then for any factor under the cube root, we extract any 3rd powers we can. Since
8=2^3 and
x^7=x^6\cdot x=(x^2)^3\cdot x, we have


\sqrt[3]{8x^7}=\sqrt[3]{2^3(x^2)^3x}=\sqrt[3]{(2x^2)^3x}=\sqrt[3]{(2x^2)^3}\cdot\sqrt[3]x=2x^2\cdot\sqrt[3]x

Then [1] =
2x^2 and [2] =
x.

User Janina
by
4.7k points